2007
DOI: 10.1007/s11606-007-0429-4
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index is Inversely Related to Mortality in Elderly Subjects

Abstract: PURPOSE:To study the long-term effect of being overweight on mortality in very elderly subjects. METHODS:The medical records of 470 inpatients (226 males) with a mean age of 81.5±7 years and hospitalized in an acute geriatric ward between 1999 and 2000 were reviewed for this study. Body mass index (BMI) at admission day was subdivided into quartiles: <22, 22-25, 25.01-28, and ≥28 kg/m 2 . Patients were followed-up until August 31, 2004. Mortality data were taken from death certificates.RESULTS: During a mean f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
4
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 46 publications
1
41
4
2
Order By: Relevance
“…Nevertheless, it is not clear whether BMI is associated with increased mortality in all populations. For example, increased BMI has not been associated with death in patients with infection admitted to a surgical ⁄ trauma intensive care unit [8], peritoneal dialysis patients [9] or hospitalized frail elderly patients [10]. The aim of the present study was to assess the effect of BMI on total and cardiovascular mortality in a very elderly population with diabetes mellitus.…”
Section: Introductionmentioning
confidence: 92%
“…Nevertheless, it is not clear whether BMI is associated with increased mortality in all populations. For example, increased BMI has not been associated with death in patients with infection admitted to a surgical ⁄ trauma intensive care unit [8], peritoneal dialysis patients [9] or hospitalized frail elderly patients [10]. The aim of the present study was to assess the effect of BMI on total and cardiovascular mortality in a very elderly population with diabetes mellitus.…”
Section: Introductionmentioning
confidence: 92%
“…In the literature cited here we find two hypotheses regarding the origin of the inverse association between BMI and mortality in the elderly most convincing (cf. Weiss et al, 2008). They have very different conclusions.…”
Section: Additional Transmission Mechanismmentioning
confidence: 99%
“…Over the past decade it was indeed found that moderate overweight is beneficial for elderly mortality, which is mostly taken as the ultimately important health marker. Several studies even find that BMI is a negative predictor of mortality (Allison et al, 1997;Janssen et al, 2005;Weiss et al, 2008;Kulminski et al, 2008;Stessman et al, 2009;Berraho et al, 2010). Allison et al (1997) observe that in the elderly BMI is convexly linked to the risk of mortality.…”
Section: Additional Transmission Mechanismmentioning
confidence: 99%
“…In contrast with middle-aged initially healthy individuals, where obesity is a strong cardiovascular risk factor, an »obesity paradox« exists among patients with multiple risk factors and a history of cardiovascular disease (45,46). Weiss et al (47) retrospectively evaluated the relationship between BMI and long-term mortality in very elderly subjects who were hospitalized in an acute geriatric ward. Patients with the lowest BMI had the highest rate of mortality even after excluding subjects who died within 6 months of hospitalization and BMI was inversely associated with mortality regardless of sex and cause of death.…”
Section: Discussionmentioning
confidence: 99%